ANALISIS PENGGUNAAN MODEL CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR MATEMATIKA MATERI BANGUN RUANG SD N TEGALOMBO 4 - Sutriyani, Wulan; Indah Sari, Noor Laila; Sa’adah, Mu’linatu (LPPM Universitas Bina Bangsa, 2024)
This research is qualitative descriptive research, which is a type of research that describes a problem in detail. The data collection technique in this study uses literature study research techniques. Literature study research techniques are a series of data collection activities by reading, recording, taking digests, and processing research data. . Based on the observations of the teaching and learning process at SD N Tegalombo 04 which is so monotonous, it is necessary to improve in terms of the learning model used by teachers. One of them is by using the Contextual Teaching and Learning learning model. . With this Contextual Teaching and Learning learning model, students not only learn material concepts using image media through student thematic books. However, students can understand the concept of the material in real terms presented by the teacher so that students get a meaningful learning experience. Learning using the Contextual Teaching and Learning (CTL) learning model in the experimental class provides a positive influence and a very large opportunity for students to more easily understand and remember teaching materials because this learning model is very suitable to be applied, so that students are enthusiastic about learning and do not cause boredom during the learning process.